Prognostic significance of peak atrial longitudinal strain in patients with functional mitral regurgitation. (4th February 2022) - Gomes, D; Lopes, P; Freitas, P; Albuquerque, F; Horta, E; Reis, C; Guerreiro, S; Abecassis, J; Trabulo, M; Ferreira, A; Ferreira, J; Ribeiras, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Chronic mitral regurgitation has been shown to promote left atrial (LA) dysfunction and remodeling. However, the significance of LA dysfunction in this setting has not been fully investigated. The aim of our study was to assess the prognostic impact of peak atrial longitudinal strain (PALS), a surrogate of LA function, in a cohort of patients with LV systolic dysfunction and functional mitral regurgitation (FMR). Methods: Patients with at least mild FMR and reduced LVEF (< 50%) under optimized medical therapy who underwent transthoracic echocardiography between 2010 and 2018 were retrospectively identified at a single-centre. FMR grading was undertaken according to the new 2021 valvular guidelines. PALS was assessed by 2D speckle tracking in apical 4-chamber view (as per EACVI current recommendations). Cox proportional hazards regression was applied for univariable and multivariable analysis to investigate the association between clinical and echocardiographic parameters, namely PALS, and all-cause mortality. Results: A total of 307 patients (median age 70 years, 77% male) were included. Median LVEF was 35% (IQR: 27 – 40%) and median mitral regurgitant volume was 25mL (IQR: 14 – 34mL). According to the new ESC 2021 valvular guidelines, 32 patients had severe FMR (10%). During a median follow-up of 3.5 years (IQR 1.4 – 6.6), 148 patients died. Median PALS was 14% (IQR 8 – 20%). The unadjusted mortality incidence per 100 persons-years increased with progressively lower values of PALS (figure 1). On ROC curve analysis, the best PALS cut-off value associated with mortality was < 15%. Kaplan-Meier survival curves according to FMR severity and PALS > or < 15% are depicted in figure 2. PALS remained independently associated with all-cause mortality on multivariable analysis (adjusted hazard ratio [aHR]: 0.94; 95%CI: 0.90 – 0.98; p = 0.004) even after adjustment for several (n = 14) clinical and echocardiographic confounders. Conclusion: In a cohort of patients with reduced LVEF and functional mitral regurgitation, peak atrial longitudinal strain was associated with all-cause mortality.